2020
DOI: 10.21608/ejchem.2020.49043.3002
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Synthesis, of Some Novel Bi-Thiazoles as Anti-Tumor Agents

Abstract: A series of novel bi-thiazoles was synthesized by reaction of 2-(1-(2-(2-(1-(4-fluorophenyl)ethylidene)hydrazinyl)-4-methylthiazol-5-yl)ethylidene) hydrazine-1-carbothioamide 3 with a variety of hydrazonoyl chloride derivatives 4a-d, and 7 a-d affording 6a-d and 9a-d respectively in dioxane in the presence of triethyl amine as a base. Also, hydrazine-1-carbothioamide 3 reacts with substituted phenacyl bromide derivatives 10 a-d yielding 12a-d in appropriate reaction conditions. The mechanisms of the titled rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
(17 reference statements)
2
1
0
Order By: Relevance
“…Over 80% of participants agreed that diagnosing CRC at an early stage can improve, which is a good sign to help motivate people who implement screening programs. This was consistent with studies previously reported in Pakistan [10] , Saudi Arabia [12] and Italy [23] . It was observed that the most common preventive practice was reducing alcohol consumption and tobacco consumption (77%), which is consistent with the results reported in the literature in China (84%) and Pakistan (69%) [10,11] .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Over 80% of participants agreed that diagnosing CRC at an early stage can improve, which is a good sign to help motivate people who implement screening programs. This was consistent with studies previously reported in Pakistan [10] , Saudi Arabia [12] and Italy [23] . It was observed that the most common preventive practice was reducing alcohol consumption and tobacco consumption (77%), which is consistent with the results reported in the literature in China (84%) and Pakistan (69%) [10,11] .…”
Section: Discussionsupporting
confidence: 94%
“…This was consistent with studies previously reported in Pakistan [10] , Saudi Arabia [12] and Italy [23] . It was observed that the most common preventive practice was reducing alcohol consumption and tobacco consumption (77%), which is consistent with the results reported in the literature in China (84%) and Pakistan (69%) [10,11] . Our study also showed an overall relationship between knowledge, attitude and screening practice towards CRC like most previous studies [14,18,22,25] .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation